The boy on the wooden box : how the impossible became possible ... on Schindler's list - Leyson, Leon, 1929-2013; Harran, Marilyn J., 1948-; Leyson, Elisabeth B. (Atheneum Books for Young Readers, an imprint of Simon & Schuster Children's Publishing Division, 2015)
Traces the story of Holocaust survivor Leon Leyson, who was the youngest child in his family and possibly the youngest of the hundreds of Jews rescued by Oskar Schindler.